The Effectiveness of "Bowen's Family System Therapy" on Differentiation and the Functions of Families with Addicted Child - Fatemeh Ghaffari; Hasan Rafiey; Mohammad bagher Sanai (Drug Control Headquarters, Research and Education Office, 2010)
Objective: The purpose of this study was to investigate the effectiveness of Bowen's Family System therapy on increasing of differentiation and improving of family function in families with addicted children. Method: The research design of this research was semi experimental design namely: pre test-post test with witness group. The sample was selected voluntarily among referred bachelor addicts and their family members in 4 therapeutic centers, and divided to experimental (5families with 4 members), and witness groups (5families with 4 members), randomly. The experimental group was under training on the basis of Bowen's family system therapy in 8 sessions. Each session was done for 2 hours. The witness group was under standard treatment of national protocols of Ministry and Health and Social Welfare Organization. The differentiation questionnaire and family function assessment were administered among two groups. Results: The result showed that Bowen's Family System therapy increased differentiation and improved the function of addicted persons and their families. Conclusion: The addicted persons and their families have low differentiation that can be caused to family dysfunction. Bowen's Family System therapy can be useful in this purpose.